Proses Perjodohan Syariah di Kantor Biro Taaruf Syar’i Kabupaten Sukoharjo Menggunakan Analisa Teori Forum Shopping dan Gender Diversity - Nahar Surur; Ikka Puspita Sari; Muhammad Alfaruq Nirwana (Asy-Syari’ah : Jurnal Hukum Islam, 2024)
Sharia matchmaking, also known as taaruf, is an effort made by an ikhwan/sister in an effort to find a partner who is in the same league. Several institutions such as the Bureau of Ta'aruf Syar'i, Sukoharjo Regency, provide this matchmaking service. However, for some people, the ta'aruf program at the Office is not only used by young people to find a life partner, but this program is also of interest to widowers to find sirri to polygamy partners. The purpose of this study is to find out how the sharia matchmaking process is in the Taaruf Syar'i Bureau Office, Sukoharjo Regency. In addition, the author also wants to know the reasons for the perpetrators of ta'aruf who choose to marry officially, marry sirri and even polygamy. The author uses a legal sociology approach in reading the phenomena that occur and analyzes using the Forum Shopping theory. In addition, the author also uses the theory of Gender Diversity in observing the domination of the parties in deciding the marriage model. In searching for primary data, the author conducted in-depth interviews with the Head of the Bureau Office and parties who have been in the Office. While secondary data, the authors obtained from related sources such as books, journals, articles, and scientific papers. From the research conducted, the authors found several reasons why some taaruf actors chose to marry legally and some others chose to marry siri or even polygamy. For perpetrators of legal marriage, they are aware of the guarantee of civil rights obtained from the orderly administration of marriage. As for the perpetrators of unregistered marriages and polygamy, they have personal interests such as economic, biological reasons, and even disappointment with the KUA's policies.